n the identification of some characters in Plano Carpini’s “History of the Mongols” - Trepavlov V.V. (Золотоордынское обозрение, 2022)
Research objectives: To identify representatives of the Mongolian ruling elite of the 13th century whose names are mentioned in the “History of the Mongols” by the Papal legate, Franciscan John (Giovanni) de Plano Carpini, as well as several historical realities of the epoch of the Mongol conquests. Research materials: The Wolfenbüttel copy of the “History of the Mongols” and its new Russian translation, Persian Arabic and Russian chronicles, Mongolian medieval writings of the 13th–17th century, historiographical literature on the Mongol Empire of the first half of the 13th century. Results and novelty of the research: Based on the comparison of information from various sources, different proposals for the identification of some characters appearing in the “History of the Mongols” by Plano Carpini have been offered. Identification of names is complicated by the abundance of their discrepancies in various editions and handwritten versions of the work under study. The basis for the present analysis was the second, lengthy edition of Plano Carpini’s work, existing in two copies that independently go back to the common protograph – the Wolfenbüttel (the 14th century) and the Cambridge (the 13th century). This article suggests the identification of the Mongol governors in the southern Russian steppes, Mautsi and Karbon, with Noyon Mugedu and an anonymous Gurgan (i.e., Batu’s son–in-law) respectively; Batu’s court dignitary Eldegai can be associated with Eldeke from the Juryat tribe. Assumptions are also made regarding the discovery of prototypes of the Mongol military commander and governor Korentsa (Kuremsa), the Khorezm ruler Altisoldan, and the town Summerkent of the “Saxes” (Saxins) people.